Photomorphogenesis in Plants and Bacteria Function and Signal Transduction Mechanisms - Schäfer, Eberhard; Nagy, Ferenc (Springer Netherlands : Imprint: Springer, 2006)
Plants as sessile organisms have evolved fascinating capacities to adapt to changes in their natural environment. Arguably, light is by far the most important and variable environmental factor. The quality, quantity, direction and duration of light is monitored by a series of photoreceptors covering spectral information from UVB to near infrared. The response of the plants to light is called photomorphogenesis and it is regulated by the concerted action of photoreceptors. The combined techniques of action spectroscopy and biochemistry allowed one of the important photoreceptors - phytochrome - to be identified in the middle of the last century. An enormous number of physiological studies published in the last century describe the properties of phytochrome and its function and also the physiology of blue and UV-B photoreceptors, unidentified at the time. This knowledge was summarized in the advanced textbook "Photomorphogenesis in Plants" (Kendrick and Kronenberg, eds., 1986, 1994). With the advent of molecular biology, genetics and new molecular, cellular techniques, our knowledge in the field of photomorphogenesis has dramatically increased over the last 15 years.